Aplicativo mobile para gerenciamento de reembolso de quilometragem - Cambruzzi, Weslei Patrick (2020)
More and more companies are reviewing their procedures, in order to remain in the competitive market in which they operate. The organization and management of costs and expenses has a great emphasis in this regard, including in the scope of modernization and computerization of processes. Aiming to reduce costs for the company, the need to computerize the mileage control process, paid for the displacement of employees of a company, when using their own vehicle for commuting to and from work. Thus, the development of an application that makes it possible to register the vehicles and, consequently, the owners who went to the company with their own vehicle, for the identification of the vehicle will be used the reading of a QR Code and finally a report of the registered information.